Application of linear friction welding for joining ultrafine grained aluminium. (August 2020) - Orłowska, Marta; Olejnik, Lech; Campanella, Davide; Buffa, Gianluca; Morawiński, Łukasz; Fratini, Livan; Lewandowska, Małgorzata
Abstract: Ultrafine grained (UFG) materials are of great potential in industry due to their enhanced mechanical strength and other promising features, such as ability to superplastic deformation or excellent corrosion resistance. Nevertheless, one of the main limitations lies in their low thermal stability, which leads to excessive grain growth at elevated temperature. It influences mainly further processes performed at high temperature, such as joining. It causes detrimental problems during conventional fusion welding, as significant grain growth is observed and therefore the advantages as a result of small average grain size disappear. Therefore, the idea of applying solid state joining process seems to be suitable for UFG materials. Among the group of solid state welding processes there are methods based on friction. One of these methods, which is suitable for samples in the form of rectangular bars, is linear friction welding (LFW). Present study is the first comprehensive work describing the results of UFG aluminium welded using LFW method with additional emphasis put on a position of shear planes of welded samples. The results have shown, that UFG regime has not been preserved in a weld zone. Welding of UFG sample with an average grain size of 1 μm resulted in a grain growth in weld zone to 1.6−2 μm. Chosen parameters allowed to weld samples only locally, nevertheless, results from tensile tests performed on mini samples showed a great potential of the LFW method for joining UFG samples. The tensile strength of welds was in the range of 83–90 % of initial material.